2016
DOI: 10.1002/lary.26104
|View full text |Cite
|
Sign up to set email alerts
|

Midline posterior glossectomy and lingual tonsillectomy in obese and nonobese children with down syndrome: Biomarkers for success

Abstract: 4. Laryngoscope, 127:757-763, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 30 publications
(75 reference statements)
0
51
0
Order By: Relevance
“…To assess the effect of AT and lingual tonsillectomy on OSA severity, 11 studies were identified for analysis [12], [43], [45], [58], [72],…”
Section: Surgery and Osa Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…To assess the effect of AT and lingual tonsillectomy on OSA severity, 11 studies were identified for analysis [12], [43], [45], [58], [72],…”
Section: Surgery and Osa Outcomementioning
confidence: 99%
“…Four additional studies were excluded due to lack of sufficient information [55], [86]- [88], one study was excluded due to reliance on symptom improvement rather than PSG [89], and three other studies were excluded because they employed more invasive surgeries [18], [59], [78]. [12], [83], [84]. Two studies utilizing an AHI of 2 as a cutoff reported normalization for 17.8% of individuals (8/45) [58], [72].…”
Section: Surgery and Osa Outcomementioning
confidence: 99%
“…10 For example, although midline posterior glossectomy with or without lingual tonsillectomy has been suggested to significantly reduce AHI in children with DS who have persistent OSA following adenotonsillectomy, these procedures can lead to postoperative bleeding as well as increased postoperative hospital stay due to poor oral intake. 11 In the case of tracheostomy, significant caregiver burden and reduced mental health are also encountered. 12 Hypoglossal nerve stimulation has emerged as a novel therapy for OSA in adults.…”
Section: Introductionmentioning
confidence: 99%
“…In syndromic children—children with underlying medical disorders—persistent OSA following AT may be due to lingual tonsil hypertrophy and/or relative macroglossia in Down syndrome, Beckwith‐Wiedemann syndrome, or velocardiofacial syndrome . However, not all of these patients are cured of their OSA following lingual tonsillectomy or midline posterior glossectomy, suggesting a role for other contributing factors . Conversely, persistent OSA following AT in healthy individuals is rarely due to lingual tonsil hypertrophy or macroglossia.…”
Section: Introductionmentioning
confidence: 99%
“…12 However, not all of these patients are cured of their OSA following lingual tonsillectomy or midline posterior glossectomy, suggesting a role for other contributing factors. 13 Conversely, persistent OSA following AT in healthy individuals is rarely due to lingual tonsil hypertrophy or macroglossia.…”
Section: Introductionmentioning
confidence: 99%